Ukrainian flora checklist. 16: families Apocynaceae (incl. Asclepiadaceae), Gentianaceae and Rubiaceae (incl. Theligonaceae) (Gentianales, Angiosperms) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Materials and methods: herbarium collections, literature data, field observations. Nomenclature: Euro+Med Plant Base 2025, Hassler 1994–2025, POWO 2025. Results: In the flora of Ukraine, the order Gentianales comprises three families: Apocynaceae (including Asclepiadaceae), Gentianaceae, and Rubiaceae (including Theligonaceae). Apocynaceae includes seven genera: Apocynum (4 species, with A. cannabinum cultivated and escaped), Asclepias (A. syriaca, invasive), Cynanchum (C. acutum), Nerium (N. oleander, cultivated in Crimea), Periploca (P. graeca, cultivated and escaped), Vinca (3 species, V. major cultivated and escaped), and Vincetoxicum (10 species and two subspecies, excluding type species, of which 4 species and 1 subspecies of uncertain status). Vincetoxicum minus, V. intermedium, and V. maeoticum are treated as synonyms of V. fuscatum, while V. cretaceum, V. laxum, and V. officinale are synonyms of V. hirundinaria. Gentianaceae includes seven genera: Blackstonia (2 species, B. acuminata requires confirmation), Centaurium (4 species, 3 subspecies, C. littorale requires confirmation), Gentiana (11 species; G. × charpentieri uncertain, G. frigida and G. clusii erroneously listed), Gentianella (3 species; G. axillaris and G. lingulata are synonyms of G. amarella), Gentianopsis (G. ciliata), Schenkia (S. spicata), and Swertia (S. perennis with 2 subspecies, S. punctata). Rubiaceae is represented by nine genera, 65 species (incl. hybrids), and six subspecies: Asperula (3 species), Crucianella (2 species confirmed, C. gilanica requires confirmation), Cruciata (5 species), Cynanchica (6 species and 3 subspecies), Hexaphylla (H. cretacea), Galium (44 species including hybrids, 3 subspecies), Rubia (R. tatarica, R. tinctorum), Sherardia (S. arvensis), and Theligonum (T. cynocrambe). Asperula propinqua is treated as a synonym of A. taurina; Crucianella oxyloba is included in C. angustifolia; C. catellata in C. latifolia. Numerous nomenclatural adjustments were made within Galium.
Keywords: biodiversity, annotated list, distribution, species, subspecies, genus, family, systematics, nomenclature, synonyms, herbarium specimens